2016
DOI: 10.1016/j.jcmgh.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis Contributes to the Delayed Gastrointestinal Transit in High-Fat Diet Fed Mice

Abstract: Background & AimsHigh-fat diet (HFD) feeding is associated with gastrointestinal motility disorders. We recently reported delayed colonic motility in mice fed a HFD for 11 weeks. In this study, we investigated the contributing role of gut microbiota in HFD-induced gut dysmotility.MethodsMale C57BL/6 mice were fed a HFD (60% kcal fat) or a regular/control diet (RD) (18% kcal fat) for 13 weeks. Serum and fecal endotoxin levels were measured, and relative amounts of specific gut bacteria in the feces were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
108
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 55 publications
10
108
1
7
Order By: Relevance
“…3,4 Normal intestinal motility involves the coordinated function of extrinsic innervation of the intestine and the enteric nervous Abstract Background: Obesity has been linked to gastrointestinal disorders, and the loss of myenteric neurons in the intestine caused by high-fat diets (HFD) has been attributed to changes in microbiota and lipotoxicity. 1 Obesity has also been associated with gastrointestinal motility disorders 2 ; constipation and longer colonic transit times are frequently observed in animal models of excessive fat intake in the diet.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3,4 Normal intestinal motility involves the coordinated function of extrinsic innervation of the intestine and the enteric nervous Abstract Background: Obesity has been linked to gastrointestinal disorders, and the loss of myenteric neurons in the intestine caused by high-fat diets (HFD) has been attributed to changes in microbiota and lipotoxicity. 1 Obesity has also been associated with gastrointestinal motility disorders 2 ; constipation and longer colonic transit times are frequently observed in animal models of excessive fat intake in the diet.…”
mentioning
confidence: 99%
“…In addition to enteric neurons, glial cells act by integrating motility control and regulating intestinal barrier function and secretion, although their exact functions and mechanisms are still poorly understood. 4,17,18 Additionally, HFDs were reported to activate inflammatory processes by increasing the production of lipopolysaccharides (LPSs) by the microbiota and activate Toll-like receptors (TLRs). Previous studies reported that HFDs significantly altered the intestinal microbiota and increased intestinal permeability.…”
mentioning
confidence: 99%
See 3 more Smart Citations